Culture and Customs of Ethiopia. - Tijani, Hakeem (Culture and customs of Africa., 2014)
An ideal resource for anyone interested in learning about Ethiopia, this accessible, single-volume work provides all-encompassing and up-to-date coverage of the ancient and diverse cultures of Africa's second-most populated nation.